Social Entrepreneurship in Tunisia : Achievements and Ways Forward - World Bank (World Bank, Washington, DC, 2017)
This paper examines the current state of the social enterprise sector in Tunisia and its potential for contributing to the country`s development objectives. The paper is based on a literature review, mapping of SEs in Tunisia, a series of interviews with social entrepreneurs and local experts, and an in-depth study of four SEs. The study draws on international policy experiences to provide conclusions and recommendations regarding the role that the government and donors could play to promote social entrepreneurship in Tunisia.